Handbook of coal analysis - Speight, James G. (Hoboken, New Jersey : Wiley, 2015)
Provides users with everything they need to know about testing and analysis of coal -Includes new coverage on environmental issues and regulations as related to coal -Provides the reader with the necessary information about testing and analyzing coal and relays the advantages and limitations in understanding the quality and performance of coal -Explains the meaning of test results and how these results can predict coal behavior and its corresponding environmental impact during use -Includes a comprehensive Glossary which defines items in straightforward language that enable readers to better understand the terminology related to coal -Treats issues related to sampling, and accuracy and precision of analysis.
9.5 GRINDABILITY9.6 OTHER MECHANICAL PROPERTIES; REFERENCES; CHAPTER 10: SOLVENT PROPERTIES AND SPECTROSCOPIC PROPERTIES; 10.1 INTRODUCTION; 10.2 SOLVENT PROPERTIES; 10.3 SPECTROSCOPIC PROPERTIES; REFERENCES; CHAPTER 11: THE NEED FOR COAL ANALYSIS; 11.1 INTRODUCTION; 11.2 IDENTIFICATION AND CHARACTER OF COAL; 11.3 PHYSICAL PROPERTIES; 11.4 PRODUCTION; 11.5 PREPARATION, TRANSPORTATION, AND STORAGE; 11.6 UTILIZATION; REFERENCES; GLOSSARY; COMMON CONVERSION FACTORS USED IN COAL TECHNOLOGY; INDEX; CHEMICAL ANALYSIS; End User License Agreement.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Coal -- Analysis -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Coal -- Analysis; Electronic books; Handbooks and manuals